Shrimp postlarvae immigration during the high current velocity period of the flood tide in the Southern Gulf of Mexico - Flores-Coto, César; Becerril-Martínez, José A.; Zavala-García, Faustino; Zavala-García, Faustino; Gracia, Adolfo; Burke, John S. (HIDROBIOLÓGICA, 2017)
The immigration pattern of shrimp postlarvae was analysed in the Santana inlet (Tabasco State, Mexico) during the high current velocity period of the flood tide at the time of the full Moon, throughout the period of greatest postlarvae abundance (April-November). Nets with a 50 cm diameter mouth, 1.5 m long, and a 505 µm mesh were used for simultaneous sampling at three depth levels: 1, surface (0.5 m), 2, mid-water (3.5 m) and 3, bottom (6.5 m). A total of 15,530 postlarvae of Farfantepenaeus duorarum and Litopenaeus setiferus were collected in 101 samples: 33 at level 1, 34 at level 2, and 34 at level 3. More than 75% of L. setiferus larvae were larger than 8 mm and more than 81% of F. duorarum were larger than 9 mm. Temperature and salinity varied only slightly, indicating that they do not play a strong role in postlarvae immigration. Postlarvae entered at all water depths. A larvae immigration pattern may be established for both species, with the greatest postlarvae density at the start of the high current velocity period of the flood tide, and a marked decrease towards the end of the period. It is assumed that this immigration pattern allows a deeper penetration into nursery areas and enhances the success of the process of recruitment into estuaries.